2021
DOI: 10.1111/evo.14307
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and mutation in Arabidopsis

Abstract: The effects of genetic mutations are influenced by genome structure. Polyploids have more gene or allele copies than diploids, which results in higher tolerance of recessive deleterious mutations. However, this benefit may differ between autopolyploids and allopolyploids and between neopolyploids and older polyploid lineages due to the effects of hybridization and diploidization, respectively. To isolate these effects, we measured the impacts of controlled mutagenesis on reproductive fitness traits in closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…In comparison to diploid organisms, tetraploids confer a significant advantage in terms of gene redundancy, acting as a protective shield against the deleterious effects of mutations by masking recessive alleles through dominant WT alleles. During the gametophytic stage, the vulnerability of haploid gametes from diploids to detrimental loss-of-function mutations is mitigated by diploid gametes from tetraploids, which can camouflage the impact of deleterious recessive alleles with additional wild-type alleles ( Immler 2019 ; Spoelhof et al 2021 ). Furthermore, at the zygotic stage, polyploidy reduces the occurrence of homozygous recessive alleles ( Stadler 1929 ; Mable and Otto 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to diploid organisms, tetraploids confer a significant advantage in terms of gene redundancy, acting as a protective shield against the deleterious effects of mutations by masking recessive alleles through dominant WT alleles. During the gametophytic stage, the vulnerability of haploid gametes from diploids to detrimental loss-of-function mutations is mitigated by diploid gametes from tetraploids, which can camouflage the impact of deleterious recessive alleles with additional wild-type alleles ( Immler 2019 ; Spoelhof et al 2021 ). Furthermore, at the zygotic stage, polyploidy reduces the occurrence of homozygous recessive alleles ( Stadler 1929 ; Mable and Otto 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some polyploids, increased mature seed size can produce a trade‐off resulting in an overall reduction of seed production and reproductive output (Porturas et al, 2019; Spoelhof et al, 2021). The polyploids in this study all produced fewer mature seeds per inflorescence than diploid T. dubius , but similar or greater amounts than T. pratensis and T. porrifolius .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with several studies that have quantified mutation effects on A. thaliana performance in laboratory conditions, where the mutagen is a single T-DNA insert (Rutter et al 2017; Murren et al 2019). Spoelhof et al (2021) found EMS induced mutations in A. thaliana to have uniformly deleterious effects on performance. However, they used a higher dosage and did not transfer the mutations through several generations (as we did).…”
Section: Discussionmentioning
confidence: 99%